Miscibility and Langmuir Studies of the Interaction of E2 (279-298) Peptide Sequence of Hepatitis G Virus/GB Virus-C with Dipalmitoylphosphatidyl Choline and Dimiristoylphosphatidyl Choline Phospholipids - Miñones, J Jr (Langmuir : the ACS journal of surfaces and colloids, 2015)
Mixed monolayers of E2(279-298), a synthetic peptide belonging to the structural protein E2 of the GB virus C (GBV-C), formerly know as hepatitis G virus (HGV), and the phospholipids dipalmitoylphosphatidyl choline (DPPC) and dimiristoylphosphatidyl choline (DMPC),which differ in acyl chains length, were obtained at the A/W interface (monolayers of extension) in order to provide new insights on E2/phospholipids interaction. Analysis of the surface pressure-area isotherms, Brewster angle microscopy images, relative thickness, and mean areas per molecule has allowed us to establish the conditions under which the mixed components of the monolayer are miscible or immiscible and know how the level of the E2/phospholipid interaction varies with the composition of the mixed films, the surface pressure, and the hydrocarbon chains length of the phospholipids. The steric hindrance caused by the penetration of the polymer strands into the more or less ordered hydrocarbon chains of the phospholipids was suggested to explain the differences in the peptide interaction with the phospholipids studied. Therefore, the novelty of results obtained with the Langmuir film balance technique, supplemented with BAM images allow us to achieve a deeper understanding of the interaction